2019
DOI: 10.1386/jaah_00005_1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and enablers for creative arts practice in care homes

Abstract: This article reports on the experiences of artists working in UK care homes across residencies that focused on poetry, dance and drama. Data were collected from reflective diaries and focus group discussions to explore the key challenges when working in settings that can be unfamiliar, complex and disruptive. We also describe a range of strategies that artists developed in response to these challenges (enablers) and how this supported successful delivery of their sessions. We conclude that artists need time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…It is hoped that these meetings can prevent some of the challenges that artists experienced in several settings, such as groups that are too large, disruption of sessions, unsuitable rooms and insufficient support from staff. Similar challenges have previously been reported by artists working in care homes (Evans et al, 2019a).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is hoped that these meetings can prevent some of the challenges that artists experienced in several settings, such as groups that are too large, disruption of sessions, unsuitable rooms and insufficient support from staff. Similar challenges have previously been reported by artists working in care homes (Evans et al, 2019a).…”
Section: Discussionsupporting
confidence: 84%
“…Arts-based activities have become an increasingly popular intervention for older people in a range of settings, and a growing number of artists are developing the skills needed to adapt their practice to settings that can be unpredictable and complex (Evans et al, 2019a). More and more UK care homes are offering opportunities to participate in meaningful activities for their estimated 500,000 residents, with the overarching aim of providing "emotional, creative, intellectual and spiritual stimulation" (National Institute of Health and Care Excellence, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study resonate with both Clark (2014) and Evans et al (2019) but also identified that the Activities Co-ordinators play a key role in overcoming this challenge. In the introduction we outlined the skills required by the Activities Co-ordinator and from the data, we identified how these skills were utilised in the programme delivery, including: organising the home and the room where the activity would happen, ensuring residents were ready and able to join the group and communicating with the residents, other members of staff and the Arts Facilitators.…”
Section: The Approach Of the Arts Facilitatorsupporting
confidence: 86%
“…Clark (2014) explored the challenges of good integrated working between the arts and care settings, and identified that the diversity between sectors and the cultural differences of the sectors, were two of the main challenges to overcome when introducing arts programmes into the care context. Recent research supports this, with the overarching culture of the care home being found to be important in determining the success of an artist in facilitating engagement of residents with meaningful activities (Evans et al, 2019).…”
Section: The Approach Of the Arts Facilitatormentioning
confidence: 94%
See 1 more Smart Citation